Draft Annual Plan (2011-2012) Part -1 (Summary) Government of Tripura - Planning Commission (Planning Commission, 2011)
The erstwhile princely State of Tripura merged with the Indian Union after independence on the 15th October, 1949 as Group-C category State. Tripura became a Union Territory without legislature with effect from November 01, 1956 and a popular ministry was installed in Tripura on July 01, 1963. Tripura became a full-fledged State on the January 21, 1972. At present, the State has 4 districts, 17 sub-divisions, 40 blocks and also one Tribal Areas Autonomous District Council (TTAADC). the TTAADC was set up in 1982 under the Seventh Schedule of the Constitution, which was then brought under the Sixth Schedule in 1985. the TTAADC covers about 2/3rd of the total area of the State. It covers all the four districts and has 1 /3rd population of the State.
Government of Tripura, Planning (P&C) Department